A Comprehensive Evaluation of ZrC Nanoparticle in Combined Photothermal and Radiation Therapy for Treatment of Triple-Negative Breast Cancer - Jiang, Shan; Liu, Zhao; Tian, Yuhang; Zhuang, Ming; Piao, Shiqi; Gao, Yan; Tam, Andrew; Hu, Hongtao; Cheng, Wen (Frontiers in Oncology, 2021)
Because of the difficulty in treating triple-negative breast cancer (TNBC), the search for treatments has never stopped. Treatment opinions remain limited for triple-negative breast cancer (TNBC). The current treatment approach of using photothermal therapy (PTT) is often imprecise and has limited penetration below the surface of the skin. On the other hand, radiation therapy (RT) has its unavoidable disadvantages, such as side effects or ineffectiveness against hypoxic tumor microenvironment (TME). In this study, we proposed the use of ZrC nanoparticles in conjunction with RT/PTT to enhance antitumor and antimetastatic effect. We modified the ZrC nanoparticle with bovine serum albumin (BSA) and folic acid (FA), sizing desirable about 100nm. The photothermal conversion efficiency was calculated to be 40.51% and sensitizer enhancement ration (SER) was 1.8. With addition of ZrC NPs, more DNA were damaged in γ-H2AX and more ROS were detected with immunofluorescence. In vitro and vivo, the combined therapy with ZrC NPS showed the best effect of tumor cell inhibition and safety. Our results provide evidence that the combination of ZrC NPs, PT, and RT is effective in of TNBC, making it a great potential application for cancer therapy in clinic.